Tennisgame Physio: A tool for amputees physiotherapy based on gamification - Pinheiro, Andrelise Nunes Lemos (2022)
The present work aims to develop a computational solution in hardware and software that uses gamification methodologies to help physiotherapy professionals in the rehabilitation sessions of upper and lower limb amputees, who are in the pre-prosthetic and prosthetic stages. Thus, a table tennis match simulator is developed to instigate patients to reach the flow state during the session. Thus, a mobile program is developed to collect data from the smartphone’s gyroscope sensor and, through Bluetooth communication with the Arduino prototyping board, this information is forwarded to the simulator. The data received is used to move the virtual racket in the game. Furthermore, physiotherapists have a tool integrated with the tennis match simulator, to monitor the progress of patients during the sessions. In short, this solution turns out to be effective in helping both patients and physical therapists in physical rehabilitation sessions.